COMPARATIVE ANALYSIS OF HYBRID CORN FARMING BASED ON BUSINESS SCALE IN TEMPUREJO SUB-DISTRICT - S, Sutimawati; Aulia, Anisa Nurina; Muliasari, Risa Martha (AGRIBEST, 2019)
Hybrid maize cultivated in an effort to meet domestic corn production, which has been importing large quantities, the objectives of this study are: (1) To compare the productivity of hybrid corn farming based on business scale. (2) To compare the advantages between hybrid corn farming scale. (3) To compare the efficiency of cost utilization in hybrid corn farming based on business scale.Data used in this research is primary data and secondary data. Data collection using interview method and questionnaire. The data collected in the analysis used the F-test and LSD test.Based on the results of the research can be concluded: (1) On land productivity between small and medium-sized narrow scale business scale shows significant difference at the 90% level of confidence, but on the scale of large area of land with narrow land indicates insignificant differences. (2)The narrow gains of moderate land indicate a significant difference in profits, whereas on a broad scale the narrow and wide scaled businesses show no significant difference in the 90% confidence level. (3) There is a difference in the level of cost efficiency between the narrow and the moderate scale indicating a significant difference at the 10% test level, but on the medium scale with broad and narrow area indicating an insignificant difference in the 90% confidence level.